Infiltrants for Aesthetic Treatment of White Spots Lesions by Fluorosis: Case Report - Pomacóndor-Hernández, César; Hernandes da Fonseca, Natália Maria Aparecida (Odovtos - International Journal of Dental Sciences, 2019)
Dental fluorosis is an abnormality in the development of enamel due to the excessive intake of fluoride during formation of dental tissues, mainly characterized by hypomineralization and increased porosity of the enamel structure. Oftenly the spots caused by dental fluorosis can compromise the aesthetics of the patient and affect their self-esteem. In recent years a new generation of dental materials has been developed, known as resin infiltrants, which are basically low viscosity resins that infiltrate and paralyze the progression of incipient non cavitated carious lesions. When resin infiltrants have been used to stop carious lesions it has been verified that they also produce changes in the appearance of white spots, masking or making them imperceptible. The present article describes a case report of the use of resin infiltrants for aesthetic treatment of white spot lesions caused by fluorosis.